In vitro interactions between 17β-estradiol and DNA result in formation of the hormone-DNA complexes - Heger, Zbynek; Guran, Roman; Zitka, Ondrej; Beklova, Miroslava; Adam, Vojtech; Kizek, Rene (International journal of environmental research and public health, 2014)
Beyond the role of 17β-estradiol (E2) in reproduction and during the menstrual cycle, it has been shown to modulate numerous physiological processes such as cell proliferation, apoptosis, inflammation and ion transport in many tissues. The pathways in which estrogens affect an organism have been partially described, although many questions still exist regarding estrogens' interaction with biomacromolecules. Hence, the present study showed the interaction of four oligonucleotides (17, 20, 24 and/or 38-mer) with E2. The strength of these interactions was evaluated using optical methods, showing that the interaction is influenced by three major factors, namely: oligonucleotide length, E2 concentration and interaction time. In addition, the denaturation phenomenon of DNA revealed that the binding of E2 leads to destabilization of hydrogen bonds between the nitrogenous bases of DNA strands resulting in a decrease of their melting temperatures (Tm). To obtain a more detailed insight into these interactions, MALDI-TOF mass spectrometry was employed. This study revealed that E2 with DNA forms non-covalent physical complexes, observed as the mass shifts for app. 270 Da (Mr of E2) to higher molecular masses. Taken together, our results indicate that E2 can affect biomacromolecules, as circulating oligonucleotides, which can trigger mutations, leading to various unwanted effects.
Keywords: DNA; lidé; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Estradiol; spektrofotometrie ultrafialová; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Spectrophotometry, Ultraviolet; estradiol; Humans